2021
DOI: 10.3390/atmos12111423
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Variations in the Temperature and Precipitation Extremes in Yangtze River Basin, China during 1961–2020

Abstract: Based on daily maximum temperature (Tmax), minimum temperature (Tmin), and precipitation of the Yangtze River Basin (YRB) from 1961 to 2020, we employed the trend analysis method and correlation analysis method to analyze spatiotemporal variations in 10 extreme indices and their associations with atmospheric and oceanic circulations. Results indicated that maximum Tmax (TXx), maximum Tmin (TNx), and minimum Tmin (TNn) all increased significantly, at rates of 0.19 °C, 0.19 °C, and 0.37 °C per decade, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…The nine precipitation indices show an overall upward trends of the intensity and frequency of extreme precipitation in the MLYR from 1979 to 2015 (Cui et al, 2012;Tian et al, 2017), which may be related to the strengthening of the East Asian summer monsoon. Both CWD and RX1day increase significantly, while R25mm, R99, PRCPTOT and RX5day showed an insignificant increasing trend (Yuan et al, 2021), and CDD tends to decrease. It means that the number of continuous dry days in the MLYR will decline, the precipitation of a single day or consecutive days will rise, both the amount of extremely heavy precipitation and the total precipitation are going to ascent, which is more likely to result in extreme precipitation events (Yu and Zhai, 2021;Yue et al, 2021).…”
Section: Temporal Variation Characteristics Of Extreme Precipitation ...mentioning
confidence: 88%
“…The nine precipitation indices show an overall upward trends of the intensity and frequency of extreme precipitation in the MLYR from 1979 to 2015 (Cui et al, 2012;Tian et al, 2017), which may be related to the strengthening of the East Asian summer monsoon. Both CWD and RX1day increase significantly, while R25mm, R99, PRCPTOT and RX5day showed an insignificant increasing trend (Yuan et al, 2021), and CDD tends to decrease. It means that the number of continuous dry days in the MLYR will decline, the precipitation of a single day or consecutive days will rise, both the amount of extremely heavy precipitation and the total precipitation are going to ascent, which is more likely to result in extreme precipitation events (Yu and Zhai, 2021;Yue et al, 2021).…”
Section: Temporal Variation Characteristics Of Extreme Precipitation ...mentioning
confidence: 88%
“…It provides Tmax, daily minimum and mean surface air temperature at 2 m, and daily total precipitation from 1961 to 2018. Previous studies have indicated that the Tmax over the YRB region exhibits an obvious shift at approximately 1980 and then increased significantly [46]. Therefore, in terms of historical periods, this study mainly focused on the characteristics of HWEs from 1981 to 2018.…”
Section: Gridded Observation Datasetmentioning
confidence: 99%
“…A majority of extreme temperature indices appear as abrupt changes since the last decades, with the main cold indices changing abruptly in the 1980s and the main warm indices changing abruptly in the late 1990s and early 2000s [40]. The maximum and minimum temperatures have increased significantly at rates of 0.19 • C and 0.37 • C per decade, respectively [41]. A recent study has reported that the magnitude of the changes in extreme climate events in the Yangtze River basin is projected to increase with the increasingly warming climate [42].…”
Section: Introductionmentioning
confidence: 99%